Pengaruh Covid-19 terhadap Indeks Harga Saham Gabungan (IHSG) dan Nilai Tukar Rupiah - Nisa Alfira; Muhammad Iqbal Fasa; Suharto Suharto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
The purpose of this study was to determine the effect of the Covid-19 pandemic on the Composite Stock Price Index (IHSG) and the rupiah exchange rate in Indonesia. The research method used is descriptive qualitative by describing the existing phenomena. The results show that the impact of the Covid-19 pandemic does not only affect public health, but also affects the Indonesian economy, especially in Islamic financial institutions in the Islamic capital market, namely the Composite Stock Price Index and the weakening of the rupiah exchange rate. The pandemic has also been proven to have put pressure on the world economy, including Indonesia.